GERAKAN PENANGGULANGAN STUNTING MELALUI PENINGKATAN PARTISIPASI MASYARAKAT MELALUI KEGIATAN SOSIALISASI DAN EDUKASI STUNTING SECARA DARING - Yulinda Laska,; Selasih Putri Isnawati Hadi,; Siti Nurlela, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Health problems should be given special attention from an early age. The most common problem in Indonesia today is stunting. Stunting is a chronic malnutrition problem caused by a lack of nutrition for a long time, resulting in impaired growth in children, namely the child’s height is lower or shorter than the height of children of their age. This service is carried out with the aim of increasing understanding and participation of the community in efforts to prevent stunting based on online socialization and education. The targets in this service are mothers who have babies and toddlers. The method used is by providing online education to mothers who have babies and toddlers about stunting prevention. The results of the activity show that the participants were actively involved in the implementation of the activity, seen when the participants were active in the question and answer session during the activity. With this community involvement, it is hoped that it will be the first step in preventing stunting and reducing the percentage of stunting in Indonesia